2014
DOI: 10.1007/s00520-014-2285-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in men receiving androgen deprivation therapy for prostate cancer: a systematic review and meta-analysis

Abstract: Purpose Prior research examining the impact of androgen deprivation therapy (ADT) for prostate cancer on cognitive performance has found inconsistent relationships. The purpose of this study was to systematically review the existing literature and determine the effect of ADT on performance across seven cognitive domains using meta-analysis. Methods A search of PubMed Medline, PsycINFO, Cochrane Library, and Web of Knowledge/Science databases yielded 157 unique abstracts reviewed by independent pairs of rater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
175
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 41 publications
4
175
1
1
Order By: Relevance
“…However, in men with PCa treated with ADT, the rate of decline in these processes appears to be accelerated (McGinty et al 2014). Furthermore, the use of ADT has been associated with an almost two-fold increased risk for developing Alzheimer's disease (AD), with the risk increasing with treatment duration (Nead et al 2016).…”
Section: The Effects Of Androgen Deprivation On Cognitive Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in men with PCa treated with ADT, the rate of decline in these processes appears to be accelerated (McGinty et al 2014). Furthermore, the use of ADT has been associated with an almost two-fold increased risk for developing Alzheimer's disease (AD), with the risk increasing with treatment duration (Nead et al 2016).…”
Section: The Effects Of Androgen Deprivation On Cognitive Functionmentioning
confidence: 99%
“…Brain imaging studies have also shown that the adverse effects to spatial ability and memory are related to changes in cerebral function and brain volume (Cherrier et al 2009, Chao et al 2012. However, a meta-analysis of 14 studies that objectively measured cognitive function in PCa survivors on ADT confirmed that the largest effect size in relation to ADT and cognitive function was for the visuomotor control domain (effect size, g = −0.67) (McGinty et al 2014), which may indicate an effect of reduced testosterone on tasks involving both vision and manual manipulation.…”
Section: :4mentioning
confidence: 99%
See 3 more Smart Citations